2016
DOI: 10.1002/chem.201602850
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Photosensitizer–Polyoxometalate‐Catalyst Dyads for Visible‐Light‐Driven Hydrogen Evolution

Abstract: A general concept for the covalent linkage of coordination compounds to bipyridine-functionalized polyoxometalates is presented. The new route is used to link an iridium photosensitizer to an Anderson-type hydrogen-evolution catalyst. This covalent dyad catalyzes the visible-light-driven hydrogen evolution reaction (HER) and shows superior HER activity compared with the non-covalent reference. Hydrogen evolution is observed over periods >1 week. Spectroscopic, photophysical, and electrochemical analyses give i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 53 publications
2
39
0
1
Order By: Relevance
“…In our previous study, we have shown that Ir‐POM Mn can be employed as homogenous light‐driven HER catalyst (see above) . Here, we investigated how variation of the central metal M affects the light‐driven HER activity of the dyads.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…In our previous study, we have shown that Ir‐POM Mn can be employed as homogenous light‐driven HER catalyst (see above) . Here, we investigated how variation of the central metal M affects the light‐driven HER activity of the dyads.…”
Section: Resultsmentioning
confidence: 87%
“…Next, we explored the covalent linkage of bpy units to { M Mo 6 } using our established synthetic protocol . Briefly, the corresponding TRIS‐Anderson was treated with 4‐methyl‐2,2′‐bipyridine‐4′‐carboxaldehyde (bpy‐CHO) in dry acetonitrile, leading to the formation of a Schiff‐base linkage between the bpy and the TRIS moiety.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations